Integrasi Prespektif Teologis dan Pedagogis dalam Pembelajaran Pendidikan Agama Islam untuk Optimalisasi Pembentukan Karakter Peserta Didik - Kurniawan, Wakib; Siti Rohmaniah; Faisol Saputra (Program Studi Pendidikan Agama Islam IAIQI Al-Qur'an Al-Ittifaqiyah, 2025)
The moral crisis affecting Indonesia's younger generation has become a serious concern in the field of education. One of the root causes is the weak internalization of spiritual and ethical values within the learning process. Islamic Religious Education (PAI), which should play a strategic role in character building, often remains confined to a purely cognitive approach. This article aims to analyze and integrate Islamic theological values with pedagogical approaches in PAI as an effort to optimize students’ character development. This research employs a qualitative approach through library research. Data were collected from a wide range of relevant literature, including academic books, journal articles, and educational policy documents. The data analysis used a descriptive-analytical method with content analysis to explore the relationship between Islamic theological concepts and pedagogical strategies in character education. The findings reveal that the integration of theological values—such as tawhid, morality, and worship—with pedagogical approaches that are humanistic, constructivist, and contextual significantly enhances the effectiveness of PAI in shaping student character. These values serve as the moral and spiritual foundation that imbues the entire learning process. The implications of this study highlight the urgency of designing a PAI curriculum that is integrative and holistic, along with the need to train teachers in pedagogical strategies aligned with Islamic theological principles. Thus, PAI can function not only as a medium for transmitting religious knowledge but also as a transformative tool for nurturing well-rounded students who are faithful, virtuous, and competitive in the modern era.